PEMBERIAN UMPAN BALIK (FEEDBACK) TES HASIL BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI - Susanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem of this research is "How Effectiveness Feedback Feeding Test Results Students Class XI IPS On Economics Subjects In Islamic High School Bawari Pontianak Year Teaching 2016/2017". To see the effectiveness of giving feedback will be done comparison between variables X1 with X2 using different test (Test T) and effect size. In this research will use 2 treatment that is the first treatment is giving feedback written, and second treatment is giving written and oral feedback. From result of SPSS test got result that at first treatment mean result of student learning 55,07 (0% completeness) before treatment become 85 (89% completeness) after given treatment. Then on the second treatment average learning outcomes from 71.83 (37% complete) before treatment to 88.26 (100% completeness) after treatment is given. Based on t test, the value of sig 0,000 <0,05 indicates that Ho is rejected or there is difference of learning result before treatment with after treatment. The value of effect size obtained is the first treatment 3.11 and the second treatment 1.91 so it can be concluded the effective feedback in improving student learning outcomes class XI IPS on economic subjects in Islamic High School Bawari Pontianak.Keywords: Feedback Feedback, Economic Learning Results